Structural and Dielectric Properties of Substituted Stannate Compounds - Ahmad Taha, Iftetan (2003)
The alkaline-earth stannates having the general chemical formula MSnO₃ ( M = Ca, Sr and Ba) have been projected as potential electronic ceramics such as thermally stable capacitors, humidity sensor, carbon dioxide sensor. There is no reliable technical information on the effect of substitutional doping on MSnO₃ system that appears to exist in the published literature. In view of the information gaps in the reported research, vigorous and systematic investigation has been carried out on two systems; SrSnO₃ and Mg₂SnO₄.